THE ROLE OF INFILTRATION WELLS FOR WATER RESOURCES CONSERVATION, CASE STUDY COMPLEX SD SUMAMPIR DISTRICT PURWOKERTO UTARA - Reni Sulistyawati AM; Pingit Broto Atmadi (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
The development of the city and the rapid population settlements that occur in urban areas, resultingin changes of land cover in the river basin that was originally able to absorb rainwater turns to make thesurface flow. With this increasingly larger surface flow, it results in flooding. Floods can be solved orreduced by reducing the surface flow by permeating to the ground. The recharge system in addition toovercoming flooding is also very beneficial for groundwater conservation efforts. The concept of the wells inits essence is to give the chance of rain water falling on the roof or water-resistant land to soak into the soilby the way of accommodating the water in a system of recation. Based on this, there is a study on theimplementation of Recation well in the water system in complex SD Sumampir, North Purwokerto District,Banyumas.Analysis conducted in this research include, hydrological analysis, dimensioning and surface flowanalysis. Data used daily maximum annual rainfall data obtained from BMKG rainfall recording station.From the results of analysis obtained the dimension of Infiltration wells with a wellbore diameter1 meter and a depth of well 2.25 meters. There is a well in the complex of SD Sumampir, North PurwokertoDistrict, can reduce the discharge of the surface flow of 0.215 mKeywords: surface flow, discharge, recation wells3/second or decrease by 40.26%.ABSTRAKPerkembangan kota dan semakin pesatnya permukiman penduduk yang terjadi di wilayahperkotaan, mengakibatkan perubahan tutupan lahan pada daerah aliran sungai yang semula dapatmenyerapkan air hujan berubah menjadikan aliran permukaan. Dengan tidak tertampungnya aliranpermukaan yang semakin besar ini mengakibatkan banjir. Banjir dapat ditanggulangi atau dikurangi dengancara mengurangi aliran permukaan dengan cara meresapkan ke dalam tanah. Sistem resapan selain dapatmengatasi banjir juga sangat bermanfaat bagi usaha konservasi air tanah. Konsep sumur resapan padahakekatnya adalah memberikan kesempatan pada air hujan yan jatuh di atap atau lahan yang kedap air untukmeresap ke dalam tanah dengan jalan menampung air tersebut padaÂ  suatu system resapan. Berdasarkanhal tersebut maka dilaksanakan Studi Penerapan Sumur Resapan pada Sistem Tata Air Di Komplek SDSumampir Kecamatan Purwokerto Utara, Kabupaten Banyumas.Analisa yang dilaksanakan dalam penelitian ini meliputi, analisa hidrologi, analisa dimensi sumurresapan dan analisa debit aliran permukaan. Data digunakan data curah hujan harian maksimum tahunanyang diperoleh dari stasiun pencatatan hujan BMKG.Dari hasil analisa diperoleh dimensi sumur resapan dengan diameter lubang sumur 1 meter dankedalaman sumur 2,25 meter. Adanya sumur di komplek SD Sumampir, Kecamatan Purwokerto Utara, dapatmengurangi debit aliran permukaan sebesar 0,215 mKata kunci : aliran permukaan, debit, sumur resapan3/detik atau berkurang 40,26%.